Adiwiyata-Based Healthy Village Training in Improving the Health of The Community Of Cangkring Village, Plumpang District, Tuban District - Sampiril Taurus Tamaji; Nely Ziyadatun Ni'mah (Shof Journal of Social Impact, 2024)
Adiwiyata-based healthy villages are villages with a program to create a society that cares and has an environmental culture. This program is implemented based on three main principles, namely educational, participatory and sustainable. This community service was carried out in Cangkring Village, Plumpang District, Tuban Regency. If we look at the geographical location, Cangkring Village is a village surrounded by rice fields, so the majority of the people farm. Apart from that, this village has the potential to be developed, one of which is the number of plants that can be used as family medicine.  The aim of this community service is to improve the level of public health in the village. The methods used in implementing the service include observation, socialization, training in making medicines from plants, and manufacturing Green House / family medicinal plant garden. The result of this service research is the availability of family land or plantations that can be managed and utilized by the community, especially by PKK mothers (family welfare development). Apart from that, the people of Cangkring Village also gained understanding and insight into the benefits of plants around them.